2013
DOI: 10.1097/inf.0b013e31828d6b20
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Controlled Trial to Assess the Immunogenicity and Safety of a Heptavalent Diphtheria, Tetanus, Pertussis, Hepatitis B, Poliomyelitis, Hib and Meningococcal Serogroup C Combination Vaccine Administered at 2, 3, 4 and 12–18 Months of Age

Abstract: The heptavalent vaccine was immunogenic and had a clinically acceptable safety profile when administered to infants and toddlers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Children received vaccines according to 1 of 4 schedules: 6, 10, and 14 weeks; 2, 3, and 4 months; 2, 4, and 6 months, or 3, 4, and 5 months. Studies were conducted in Europe (Spain France, Germany, Greece, Poland Czech Republic, Finland), Africa (Mali and Nigeria), Latin America (Chile, Nicaragua, Argentina, Dominican Republic) East Asia (The Philippines and Korea), Russia, and Australia …”
Section: Resultsmentioning
confidence: 99%
“…Children received vaccines according to 1 of 4 schedules: 6, 10, and 14 weeks; 2, 3, and 4 months; 2, 4, and 6 months, or 3, 4, and 5 months. Studies were conducted in Europe (Spain France, Germany, Greece, Poland Czech Republic, Finland), Africa (Mali and Nigeria), Latin America (Chile, Nicaragua, Argentina, Dominican Republic) East Asia (The Philippines and Korea), Russia, and Australia …”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous administration of more than one vaccine using different anatomical sites helps to reduce the number of visits and increases compliance with the recommended immunisation schedule. Moreover, several studies have demonstrated that administering these two vaccines at the same time did not interfere with the infant's immune responses and did not dramatically increase reactogenicity . To resolve paediatricians' doubts about providing more than one vaccine at a time, targeted information on the safety and immunogenicity of vaccine co‐administration needs to be provided to reduce the chance of missed opportunities for vaccinations.…”
Section: Discussionmentioning
confidence: 99%
“…Although vaccine studies have reported on the attitudes towards the electroporation procedure itself [6,9], they have done so across participants in aggregate; none have examined attitudes in the same participants over the course of a series of vaccinations. Most vaccinations will require multiple doses to achieve optimal immunogenicity and efficacy [10,11]. Therefore, it is important to explore individual participants' attitudes to the level of pain and its acceptability as a series of procedures; strong negative perceptions could impact a patient's willingness to be vaccinated or return for a full vaccination series.…”
Section: Introductionmentioning
confidence: 99%